Gender stereotypes as an obstacle to equality of opportunities between men and women in employment – possible legal contributions for solving the problem - Gonçalves, Luísa Andias (2020)
Equality between men and women has long been legally established in national and international acts. As men and women show differences capable of undermine the equality between them in what regards to the opportunities they enjoy in the labor market, the equality established by law must be understood as a substantial equality, and not a merely formal one. A State truly committed to the goal of equal opportunities has the obligation to make the distinction in treatment between the sexes when it is necessary to correct inequalities of opportunities and hence achieve real equality. The analysis of the current reality shows us that the real equality is still unachieved. It happens due to sociological barriers that are preventing the achievement of equality legally established. Those are related to the system of gender (male and female) deeply rooted and that still puts the female in a position inferior to men. Studies were conducted in sociology to explain that the current «genders system» remain through coercive and voluntary factors and that the key factor for the maintenance and, consequently, for the change, lies in the sexual division of labor between the sexes, especially in the division of housework and labor market. Changes in this field would positively contaminate the whole «genders system». So, contrary to what has been done so far, instead of continuing to protect women, often sustaining gender stereotypes and creating the 'boomerang' effect that jeopardizes equality, the way to go should pass through establishing the men preferential treatment under the assumption of family responsibilities, inclusively by the adoption of temporary positive action measures appropriated and proportionate to this purpose. Important is however that these measures still leave a margin of self-organization to the families, in order to respect individual and conjugal liberty and not to endanger the interests of third persons, such as the children. Within the labor market, the division of work between the sexes can also be promoted with measures that encourage both sexes to choose areas where they are underrepresented.